Seeds to Plants - Bates, Jeffrey frey50 (Gloucester Press New York, 1990)
Explores the biology of seeds and how they develop into plants
Includes index
Keywords: Plants -- Juvenile literature; Seeds -- Juvenile literature; Plants -- Development -- Juvenile literature; Plants -- Development; Seeds; Experiments